Non-Exercise Activity Thermogenesis (NEAT) and Prediabetes Risk Among Adolescents - Ayu Citra Mayasari; Imroatul Farida; Ceria Nurhayati; Renata Deby (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
Introduction: Prediabetes is a metabolic condition characterized by elevated blood glucose levels that do not yet meet the criteria for type 2 diabetes. Non-Exercise Activity Thermogenesis (NEAT), which includes daily physical activities outside structured exercise, plays a crucial role in energy expenditure and glucose metabolism. Adolescents are particularly vulnerable to sedentary lifestyles, which may increase the risk of prediabetes. Objective: This study aimed to examine the relationship between NEAT and prediabetes among adolescents at SMAN 1 Menganti, Gresik. Methods: A correlational analytic study with a cross-sectional design was conducted involving (n =101) students aged 15–18 years. NEAT was assessed using the Mifflin-St Jeor equation and daily activity questionnaires, while prediabetes status was determined via fasting blood glucose measurements. Data were analyzed using Spearman’s Rank Correlation, with a significance level of p < 0.05. Results: The results revealed a significant negative correlation between NEAT levels and prediabetes status r = 0.751, p = 0.009. Adolescents with lower NEAT levels had higher fasting blood glucose levels, indicating a greater risk of prediabetes. Conclusion: Enhancing NEAT through daily physical activities outside structured exercise may serve as an effective preventive strategy to reduce prediabetes risk among adolescents. School-based interventions promoting movement throughout the day are recommended to improve long-term metabolic health.